GAMBARAN MOTIVASI BELAJAR MAHASISWA BK FKIP UNDANA MENGIKUTI PEMBELAJARAN BERBASIS DARING SELAMA MASA PANDEMIC - Andriani Paulin Nalle; Khetye Romelya Saba; Lolang Maria Masi (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
The purpose of this research was to describe the learning motivation of Guidance and Counseling (BK) students of FKIP Undana in taking online lectures during the pandemic. The research approach used a mixed method, quantitative and qualitative researches. The data was collected through an accessible online questionnaire (google form) on 94 BK students and through Focused Group Discussion (FGD) with 10 students of semester III, V and VII of Guidance and Counselling’s. The results of data analysis showed that the learning motivation of BK students in taking online lectures is in the high category and has a very good percentage. It is hoped that the implementation of online learning during this pandemic can be more effective by paying attention to the delivery media, infrastructure and presenting learning that can arouse student learning motivation.